Implementasi Peraturan Daerah Nomor 3 Tahun 2010 tentang Penanggulangan Human Immunodeficiency Virus (HIV) dan Acquired Immuno Deficiency Syndrome (AIDS) di Kabupaten Semarang - Diyannita Indah Kurniasari; Wiwik Widayati; Lusia Astrika (Journal of Politic and Government Studies, 2014)
Jurusan Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu PolitikUniversitas DiponegoroJl. Prof. H. Soedarto, SH, Tembalang, Semarang, Kotak Pos 1269Website : http://www.fisip.undip.ac.id / Email : fisip@undip.ac.idAbstractSemarang regency is one of regencies in Central Java which has high risk of Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome (HIV-AIDS) transmission. Factors that cause it is because there is a high potential tourist attractions and places of prostitution in Semarang regency. Therefore, local goverment make local regulations number 3 in 2010 which contained of HIV prevention to decrease HIV transmission in Semarang regency. Besides, this regulation aimed to persuade people to concern and prevent about HIV transmission actively.The objective of this study to know the implementation of local regulations number 3 in 2010 which contained of HIV preventions in Semarang regency and obstacles since the regulations has been applied. This study using a qualitative design with descriptive method. The results of this research were analyzed based on Edward’s III theory about four variables to observe the implementation of the policy ; communication, resource, disposition, and bureaucracy structure.Communication is carried out by AIDS commission and related institution through socialization to the target groups such as HIV-AIDS sufferer, high-risk persons who can be infected HIV-AIDS, and people around the regency of Semarang. Resources variables are divided into two parts; human and financial resources. AIDS commission and health workers as human resources who have interaction with the target groups. Meanwhile, financial resources obtained from regional budget and global fund as foreign aid. In disposition aspect has been well done. It can be observed from services given by AIDS commission and related institution to HIV-AIDS sufferer. Many training are also conducted to improve commitment and ability of health workers. In bureaucracy structure, indicate that government has a long2bureaucracyal structure because of HIV-AIDS preventions are complex problems and many people have to get involved.In the other hand, the implementation of local regulations have some barriers from each variables. Communication barriers due to the education level of sex workers is low. It can influence lack of knowledge in understanding socialization. From the aspect of resources, especially financial resources, occurred the threat because of foreign aid from the global fund will be dismissed in 2015. For disposition aspect, people still get unsatisfactory services. Meanwhile, the structure of bureaucracy barriers caused by the lack of a decree that governs the law technically in 2013. In addition, stakeholders in the AIDS commission bureaucratic structure has not been completely perform basic tasks functions of HIV-AIDS preventions.The implementation of local regulations number 3 in 2010 about HIV-AIDS preventions in Semarang regency has been applied well by AIDS commission and related institution. However, there needs to be increased in disposition and bureaucratic structure. Long bureaucratic structure in AIDS commission is not expected to be an obstacle in implementing the law. Therefore, the need for cooperation by all institutions which are involved in AIDS commission in order to carry out basic tasks in accordance with the responsibilities. By the implementation of the main function of AIDS commission optimally, HIV-AIDS transmission can be minimized and the implementation of local regulation provide a positive impact to the community.Keywords : Implementation, prevention, HIV-AIDS